The psychedelic (−)-2,5-dimethoxy-4-iodoamphetamine [(−)-DOI] demonstrates efficacy in reducing cocaine reward and motivation in male rats - Leah M. Salinsky; Christina R. Merritt; Erik J. Garcia; Robert G. Fox; Joshua C. Zamora; Noelle C. Anastasio; Kathryn A. Cunningham (Psychopharmacology, 2025)
Rationale and objectives Overdose fatalities involving cocaine continue to rise with over 5.3 million cocaine users reported in the United States in 2022. The abuse liability of cocaine is reliant upon inhibition of dopamine ( DA ) reuptake and consequent increase in DA efflux in meso-corticolimbic circuitry that controls reward and motivation. Cocaine also increases serotonin ( 5-HT ) efflux which is integral in cocaine abuse. The 5-HT 2A receptor ( 5-HT 2A R ) is a key regulator of meso-corticolimbic DA release and controls cellular mechanisms underlying cocaine effects. 5-HT 2A R actions contribute importantly to psychedelic mechanisms of action, and the efficacy of these compounds in limiting cocaine intake is unknown. The present studies evaluated the efficacy of acute administration of a psychedelic to reduce cocaine intake using standard and advanced preclinical models of drug self-administration. Methods Both a standard fixed ratio ( FR ) schedule and behavioral economics threshold procedure of cocaine intravenous self-administration were employed to evaluate the efficacy of the psychedelic 5-HT 2A R agonist (−)-2,5-dimethoxy-4-iodoamphetamine [ ( − )-DOI ] to decrease cocaine intake and motivation for cocaine in male rats. The 5-HT 2A R-selective antagonist M100907 was utilized to explore the role of 5-HT 2A R in the effects of (−)-DOI on cocaine intake. Results We found that (−)-DOI dose-dependently reduced intake on the FR5 schedule of cocaine IVSA and left shifted the demand curve to evoke greater sensitivity to price increases in the behavioral economics paradigm. Pretreatment with M100907 abated the efficacy of (−)-DOI on cocaine intake in both paradigms. Conclusion (−)-DOI ‘devalued’ cocaine reward and motivation to take cocaine in a 5-HT 2A R-dependent manner. As serotonergic psychedelics emerge as therapeutic candidates, investigations of 5-HT 2A R-acting psychedelics in preclinical analyses of cocaine intake and relapse vulnerability during abstinence will be valuable as prelude to future clinical trials.